Optimalisasi Perawatan Air Conditioner Guna Menjaga Suhu Udara Di Ruang Akomodasi Pada Kapal Mt Tanker Lineo 101 - Riyadi Dwi Prasetyo, Guntur; Narto, Amad; Sulistiyowati, Ely; Yuli Aryani, Desy (Indonesian Journal of Marine Engineering, 2024)
Air conditioner (AC) is a device or system designed to change the temperature and humidity of the air in a room to create comfortable air conditions. The main function of an air conditioner is to cool the air when the outdoor temperature is too high and to remove excess humidity when the air is too humid. The research method used in this thesis is qualitative. Data sources were obtained from primary and secondary data collection. Data collection techniques used observation, interviews, literature study, and documentation. The data analysis technique used in this research is the Miles and Huberman method. They are testing the validity of the data using the triangulation method. The research results stated that the factors causing the lack of Air Conditioner maintenance on MT ships. Tanker Lineo 101 is a lack of maintenance of the Main Air Conditioner resulting in damage to components caused by non-compliance with the Plan Mantenance System (PMS). The suggestion from the researchers is that the ship and the company should further improve maintenance routines in accordance with the Plant Maintenance System (PMS) so that costs are not excessive and if the Main Air Conditioner is damaged, the person in charge should carry out repairs according to the instructions provided in the manual book Air conditioner (AC) adalah perangkat atau sistem yang dirancang untuk mengubah suhu dan kelembapan udara di dalam sebuah ruangan untuk menciptakan kondisi udara yang nyaman. Fungsi utama dari air conditioner adalah untuk mendinginkan udara pada saat suhu di luar ruangan terlalu tinggi dan untuk menghilangkan kelembapan berlebih pada saat udara terlalu lembab. Metode penelitian yang digunakan adalah metode kualitatif. Sumber data yang diperoleh dari pengumpulan data primer dan sekunder. Teknik pengumpulan data meliputi observasi, wawancara, studi pustaka dan dokumentasi. Teknik analisis data yang digunakan dalam penelitian ini adalah metode Miles and Huberman. Pengujian keabsahaan data dengan menggunakan metode triangulasi. Dari hasil penelitian diketahui penyebab minimnya peralatan AC di kapal. Pada kapal tanker "Lineo 101", sistem pendingin udara utama tidak dirawat dan bagian-bagiannya rusak karena tidak mematuhi jadwal perawatan "PMS". Saran dari penelitian ini adalah pihak kapal serta pihak perusahaan agar lebih meningkatkan rutinitas perawatan sesuai dengan Plant Mantenance System (PMS) agar biaya tidak berlebih dan bila Main Air Conditioner mengalami kerusakan, sebaiknya penanggung jawab melakukan perbaikan sesuai intruksi yang di berikan manual book.